MATHEMATICAL STUDY OF WEIGHTED TWO PARAMETERS EXPONENTIAL DISTRIBUTION - Mizaal, Awatif Rzzoky (MAGISTRA, 2015)
This paper deals with studying a weighted exponential distribution with two parameters ( ) shape parameter ( ) and ( ) scale parameter ( ), and deriving itâs cumulative distribution function, reliability function, also deriving the estimators by maximum likelihood method and moment estimator which are found after deriving the moment generating function and obtaining . Also we try to use two parameters ( ) as well as the reliability function using different sample size ( ), comparison has been done using mean square error, all results explained by tables. Keywords: Weighted exponential distribution, scale and shape parameters, cumulative distribution function, reliability function, MLE, MOM.